Changes in population structures of the major species in selected satellite lakes around Lake Victoria following changes in fishing effort - Katunzi, E F B; Kishe, M A (Tanzania Journal of Science, 2021)
This paper evaluates the impacts of reduction in effort, increase in mesh sizes, and prohibition of illegal fishing gears in selected satellite lakes around Lake Victoria. The study was carried out in six satellite lakes by making investigations on fish collected from experimental and artisanal fisheries. The fishes were analysed for length frequencies, weight and numbers caught to determine the population structure of the fishes. Indiscriminate fishing by deploying illegal gears and increased fishing effort due to open access policy, the catch and diversity of the species in these lakes has declined. Establishment of Conservation Management Units (CMUs) as an enforcement measure in some satellite lakes seems to succeed in controlling the illegal practices and a positive sign of recovery of some species and size increase of the exploitable fish species was noted in lakes Ikimba and Kirumi where enforcement has been effected. From March 2002 to January 2003 the maximum size of Oreochromis niloticus and O. esculentus had increased from 28 cm to 33 cm and 25 cm to 27 cm in Lake Kirumi and Lake Ikimba, respectively. Nevertheless, fish species diversity in these lakes is still low. Recommendations on the way forward are given